2018
DOI: 10.1074/jbc.ra117.001352
|View full text |Cite
|
Sign up to set email alerts
|

A long noncoding (lnc)RNA governs expression of the phosphate transporter Pho84 in fission yeast and has cascading effects on the flanking prt lncRNA and pho1 genes

Abstract: The expression of the phosphate transporter Pho84 in fission yeast Schizosaccharomyces pombe is repressed in phosphate-rich medium and induced during phosphate starvation. Two other phosphate-responsive genes in S. pombe (pho1 and tgp1) had been shown to be repressed in cis by transcription of a long noncoding (lnc) RNA from the upstream flanking gene, but whether pho84 expression is regulated in this manner is unclear. Here we show that repression of pho84 is enforced by transcription of the SPBC8E4.02c locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…In this study we focus on genetic connections between the CTD and factors implicated in 3′-end formation and/or transcription termination. We do so in light of previous findings that CTD phospho-sites Thr4, Ser5, and Ser7 govern the expression of fission yeast genes involved in phosphate homeostasis (6,(8)(9)(10)(11). The S. pombe phosphate regulon comprises three genes that specify, respectively, a cell surface acid phosphatase (Pho1), an inorganic phosphate transporter (Pho84), and a glycerophosphate transporter (Tgp1) (12).…”
Section: Significancementioning
confidence: 95%
“…In this study we focus on genetic connections between the CTD and factors implicated in 3′-end formation and/or transcription termination. We do so in light of previous findings that CTD phospho-sites Thr4, Ser5, and Ser7 govern the expression of fission yeast genes involved in phosphate homeostasis (6,(8)(9)(10)(11). The S. pombe phosphate regulon comprises three genes that specify, respectively, a cell surface acid phosphatase (Pho1), an inorganic phosphate transporter (Pho84), and a glycerophosphate transporter (Tgp1) (12).…”
Section: Significancementioning
confidence: 95%
“…The S. pombe Pol2 CTD consists of tandem repeats of a heptapeptide Y 1 S 2 P 3 T 4 S 5 P 6 S 7 . CTD mutations S7A and S5A that prevent installation of the Ser7-PO4 or Ser5-PO4 marks de-repress pho1 and pho84 in phosphate-replete cells (7,8,10,13). By contrast, prevention of the Thr4-PO4 mark by T4A hyper-represses pho1 and pho84 under phosphate-rich conditions (7,13).…”
Section: Introductionmentioning
confidence: 99%
“…The phosphate regulon in the fission yeast Schizosaccharomyces pombe comprises three genes that specify, respectively, a cell surface acid phosphatase Pho1, an inorganic phosphate transporter Pho84, and a glycerophosphate transporter Tgp1 (3). Expression of pho1, pho84, and tgp1 is actively repressed during growth in phosphate-rich medium by the transcription in cis of a long noncoding (lnc) RNA from the respective 5' flanking genes prt, prt2, and nc-tgp1 (4)(5)(6)(7)(8)(9)(10). It is proposed that transcription of the upstream lncRNA interferes with expression of the downstream mRNA genes by displacing the activating transcription factor Pho7 from its binding site(s) in the mRNA promoters that overlap the lncRNA transcription units (8,10,11) (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast, lncRNA can dynamically regulate pho1 expression by recruiting RNAi and the exosome on the basis of phosphate levels [12]. Moreover, lncRNA not only governs the expression of the phosphate transporter gene Pho84 but also exerts linkage effects on prt lncRNA and pho1 genes in flanking regions [13]. Recent studies have shown that lncRNAs exert a non-cell-autonomous response to P deficiency and may act as systemic signaling agents at the whole-plant level to coordinate early P deficiency signals [14].…”
mentioning
confidence: 99%